Electronic display devices: A study on screen display towards the health issues among Malaysian university students - Chen, Ai Hong; Rosli, Saiful Azlan (Journal of ICT in Education, 2022)
Excessive exposure to digital technology has been linked to adverse physical, social, and mental health. Questions have been raised about the impact of electronic devices with a drastic shift to online learning in education. This article aimed to investigate the impact of digital technology in the education setting using a mixed-method approach: laboratory-based exploration and an online survey. First, we compared the illumination profile of the screen display in comparison to traditional hardcopy materials. The luminance and spectrum profiles of smartphones and laptops were studied using the 2D Color Analyzer CA-2500 and illuminance spectrophotometer CL-500A. Second, we surveyed the digital usage profile of university students from six different universities to gather information on the total hour of daily digital engagement and the incidence of digital eye strain. The surface luminance for smartphone is 94.76 ± 11.46 cd/m2) and laptop (250.28 ± 22.88 cd/m2). The surface luminance of smartphones rises by 7% in comparison to hardcopy surfaces. The surface luminance of laptops upsurges by 203% in comparison to hardcopy surfaces. The digital engagement time of university students is about 12.80 ± 3.47 hours per day. Digital eye strain is approximately 22.15%. Self-luminosity screen displays from electronic devices emitted more luminance compared to the hardcopy materials. The electronic surface has low luminance uniformity compared to the hardcopy surface. University students exhibit high digital usage patterns and are susceptible to digital eye strain. The long-term accumulative effects of the high illuminance profile, digital engagement inclination and uprising digital eye strain from our cross-section study require further investigation.